Earthquake Activities Along the Strike-Slip Fault System on the Thailand-Myanmar Border - Santi Pailoplee (Terrestrial, Atmospheric and Oceanic Sciences, 2014)

(untitled)
This study investigates the present-day seismicity along the strike-slip fault system on the Thailand-Myanmar border. Using the earthquake catalogue the earthquake parameters representing seismic activities were evaluated in terms of the possible maximum magnitude, return period and earthquake occurrence probabilities. Three different hazardous areas could be distinguished from the obtained results. The most seismic-prone area was located along the northern segment of the fault system and can generate earthquakes of magnitude 5.0, 5.8, and 6.8 mb in the next 5, 10, and 50 years, respectively. The second most-prone area was the southern segment where earthquakes of magnitude 5.0, 6.0, and 7.0 mb might be generated every 18, 60, and 300 years, respectively. For the central segment, there was less than 30 and 10% probability that 6.0- and 7.0-mb earthquakes will be generated in the next 50 years. With regards to the significant infrastructures (dams) in the vicinity, the operational Wachiralongkorn dam is situated in a low seismic hazard area with a return period of around 30 - 3000 years for a 5.0 - 7.0 mb earthquake. In contrast, the Hut Gyi, Srinakarin and Tha Thung Na dams are seismically at risk for earthquakes of mb 6.4 - 6.5 being generated in the next 50 years. Plans for a seismic-retrofit should therefore be completed and implemented while seismic monitoring in this region is indispensable.